PENGARUH PENGAWASAN DAN PELATIHAN TERHADAP KINERJA KARYAWAN DEPARTEMEN FINISHING CV LAKSANA KAROSERI UNGARAN, KAB. SEMARANG - Huda, Addin Khoiri; Nugraha, Hari Susanta (Jurnal Ilmu Administrasi Bisnis, 2019)
employee performance affects for the continuity of the company's business, the company needs to pay attention to its employees in order to be able to work in accordance with the company's goals.several things that can be affect employees performance include supervision and training. The type of research used is Explanatory research, 67 sample out of 201 employees of CV Laksana Finishing Department with a sampling technique that is simple random sampling. the resultsof statistical test showed the correlation coefficient of supervison is 0.421 and training is 0.463 and have t count> t table, and supervision 3,746 and supervision 4,216, indicating supervision and training haveÂ  a significant and positive influence on employee performance. The coefficient of determination for supervision and training together contributes 25% of the overall performance of Finishing Department. Advise given by making news for rules violators and training must change from fundamental focus to progressive training and focus on improving quality of product.